Contextual Form Based Coding as a Tool in Urban Design Process-chalai, Thiruvananthapuram as a Case. (2016) - Shaji, Lakshmi S.; Kini, Manoj Kumar
Abstract: The present urbanized world is on a vogue to remold its impression and character into someone else's. The new impressions often carries a complete disconnect from its roots which gradually loses its self and identity and never has a sustenance. In this context Form Based Coding(FBC) as a tool in Urban Design Process aids to come up with solutions whichstrongly holds the people to their community and closelyassociated with culture through the physical spaces they areassociated with. The paper has made an effort to analyze theprocess of FBC as a genuine tool to establish the association ofphysical form and spaces with the public realm to uphold thecontext and culture by taking a case in the heritage rich centralcommercial core of Thiruvananthapuram city, Chalai. Chalai isundergoing a tremendous transformation in its physical formdisregarding its strong culture and context and this can influencethe inherent native character of the bazaar activity and looses itsidentity in form and function. In this regard form Based Codingwill be a suitable tool to strengthen it as a native bazaar for thecity. A detailed documentation of form in relation with the existing layers of street pattern, activity, building types, and function is analysed and its influences to variations in form is studied. The existing codes of the built form of different uses were decoded. The comparison of existing codes with the theoretical parameters from literature and case studies lead to the formulation of codes with FBC as a tool suitable for the context.